Analysis of Budgeting and Variance of the Operating Budget with Realization at PT Angkasa Pura I (Persero) Ngurah Rai Commercial Strategic Business Unit in Badung for Year 2017 - D M S Dewanta; I M A Putrayasa; P Subiyanto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2018)
This research aims to know the budgeting and the cause of variance between operating budget and realization at PT Angkasa Pura I (Persero) Ngurah Rai Commercial Strategic Business Unit. The data analysis technique used in this research are quantitative analysis and descriptive qualitative analysis. Result of this research showed that PT Angkasa Pura I (Persero) Ngurah Rai Commercial Strategic Business Unit perform budgeting using mixed method (Top Down and Bottom Up) with procedures and budgeting reference which already accordance with the board of directors decision and budgeting theory. The cause of operating income variance are tenant factor, recording, parking rate, and natural disaster. The cause of operating cost variance are employee factor, program, and natural disaster.